Víctimas de maltrato y su relación con la hipoprosexia de los niños y niñas del cuarto y quinto año de Educación Básica de la Escuela Luis Antonio Erique Ortega del Barrio el Plateado, de la ciudad de Loja. Periodo mayo-junio 2015 - Angamarca Tene, Amada (2015)
The present investigation has as purpose determine the degree of relation between the infantile mistreatment and the hipoprosexy, evaluate the type of disorder of attention on children, and elaborate psychological education plan directed to the Children`s parents that are cursing fourth and fifth year of basic education of the school Luis Antonio Erique Ortega directed to providing basic information about the infantile mistreatment. The investigation was of descriptive transverse type, with approach quantitative and qualitative and descriptive that handles scientific methods as: inductive deductive method, analytical synthetic method. The instruments used to reach the aims are: the battery “Mi familia y yo” directed to find mistreatment victims, The Toulouse Piéron's test to evaluate the type of disorder of the attention that the students present. With the instruments it was possible determinate the existence of physical mistreatment with a higher proportion in the masculine kind, the psychological and sexual mistreatment with highest percentage in the feminine kind. The attention disorders identified were: hipoprosexy in 32 % percent in the masculine kind and 18 % percent in the feminine kind followed by the aprosexy. The above mentioned results allow concluding that the children and girls who present three types of mistreatment: physical, psychological and sexual demonstrate as well disorders of the as hipoprosexy and the aprosexy showing an evident relation between both variables. Keywords: Hipoprosexy, aprosexy, Disorders and violence.